Silencing Rac1 and Prex1 Inhibit Epithelial–Mesenchymal Transition in Human Gastric Cancer Cells Induced by Transforming Growth Factor-β1 - Gao, Xinyan; Lin, Xiaoyan; Lin, Mengxin; Lan, Yanqin; Wang, Yao; Wu, Riping; Li, Junde; Huang, Chuanyong; Zhong, Dongta (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Transforming growth factor-beta can influence tumor cells, causing epithelial–mesenchymal transition and enhancing their invasion and metastasis ability. Rac1 protein could be used as an independent tumor diagnostic marker and survival predictor. Prex1 is closely related to cell metastasis. In this study, the impact of silencing Rac1 and Prex1 on transforming growth factor-beta 1-induced epithelial–mesenchymal transition and apoptosis of human gastric cancer cells MGC-803 and MKN45 was investigated. Materials and Methods: MGC-803 and MKN45 cells received recombinant transforming growth factor-beta 1 (rTGF-β1) treatments at various concentrations. Cell Counting Kit-8 kit was used to determine cell viability. Rac1 and Prex1 interference vectors were transfected into the rTGF-β1-treated MGC-803 and MKN45 cells. Cell apoptosis and migration were detected by flow cytometry and scratch test, respectively. Western blot was used to detect the epithelial–mesenchymal transition-related markers E-cadherin, N-cadherin, vimentin, and PDLIM2 expression levels. Results: The rTGF-β1 (10 ng/mL) could promote MGC-803 and MKN45 cell viability. Silencing Rac1 and Prex1 could increase E-cadherin and PDLIM2 expression, decrease N-cadherin and vimentin expression, inhibit cell viability and migration, and promote apoptosis in rTGF-β1-treated MGC-803 and MKN45 cells. Conclusions: Silencing Rac1 and Prex1 could inhibit epithelial–mesenchymal transition, reduce cell viability and migration, and promote apoptosis in human gastric cancer cells. Cite this article as: Gao X, Lin X, Lin M, et al. Silencing Rac1 and Prex1 inhibit epithelial–mesenchymal transition in human gastric cancer cells induced by transforming growth factor-β1. Turk J Gastroenterol. 2023;34(9):975-981.